The T-Box factor TBX3 is important in S-phase and is regulated by c-Myc and cyclin A-CDK2 - Willmer, Tarryn (Cell Cycle, 2015)
The transcription factor, TBX3, is critical for the formation of, among other structures, the heart, limbs and mammary glands and haploinsufficiency of the human TBX3 gene result in ulnar-mammary syndrome which is characterized by hypoplasia of these structures. On the other hand, the overexpression of TBX3 is a feature of a wide range of cancers and it has been implicated in several aspects of the oncogenic process. This includes its ability to function as an immortalizing gene and to promote proliferation through actively repressing negative cell cycle regulators. Together this suggests that TBX3 levels may need to be tightly regulated during the cell cycle. Here we demonstrate that this is indeed the case and that TBX3 mRNA and protein levels peak at S-phase and that the TBX3 protein is predominantly localized to the nucleus of S-phase cells. The increased levels of TBX3 in S-phase are shown to occur transcriptionally through activation by c-Myc at E-box motifs located at −1210 and −701 bps and post-translationally by cyclin A-CDK2 phosphorylation. Importantly, when TBX3 is depleted by shRNA the cells accumulate in S-phase. These results suggest that TBX3 is required for cells to transit through S-phase and that this function may be linked to its role as a pro-proliferative factor.